High-toughness low-dielectric epoxy resin prepreg for automatic fiber placement and preparation method thereof
Patent Information
- Application Number
- CN202611236088.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的目的在于提出一种自动铺丝用高韧性低介电环氧树脂预浸料及其制备方法,以解决现有环氧树脂预浸料难以兼顾低介电透波性、纤维浸润性、高损伤容限能力和自动铺丝工艺性的问题,达到低介电、高成型质量、高损伤容限和长操作寿命的效果
(1)本发明提供了一款兼具低介电功能性、高损伤容限能力以及优异自动铺丝工艺性的环氧树脂预浸料。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This article provides a high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement and its preparation method, belonging to the field of resin-based composite material preparation technology. Background Technology
[0002] With the increasing maturity of automated manufacturing technologies for composite materials abroad, automated fiber placement technology, characterized by "high efficiency, high quality stability, and high reliability," has been widely applied in various aerospace components. Due to the high maturity of the material systems used in automated fiber placement molding, the good inheritance of design molding methods, and ease of digital and automated manufacturing, it has become the main molding method for large composite material components in aircraft in developed countries. To improve the precision and efficiency of large-scale molding, automated fiber placement processes are gradually becoming the mainstream choice for molding primary / secondary load-bearing structural components. These structural components also require high load-bearing capacity and damage tolerance; their composite materials should meet high toughness requirements, with the key indicator being compressive strength after impact (CAI). Simultaneously, to achieve structural / wave-transparent and structural / stealth integration, these components also need to meet electromagnetic functionality requirements, which necessitates that the prepreg used has good low dielectric and high wave-transparent capabilities. Therefore, there is an urgent need to develop an epoxy resin prepreg that combines low dielectric functionality, high damage tolerance, and excellent automated fiber placement processability.
[0003] Epoxy resin is one of the resin matrices used in structural composites due to its excellent processability and mechanical properties. However, because epoxy resin contains a large number of polar structures, its microwave transmission performance cannot meet the application requirements. Therefore, it is necessary to modify the epoxy resin formulation to have low dielectric properties, and at the same time, it is also necessary to improve the wettability of the prepreg to eliminate interfacial polarization, thereby improving the dielectric properties of the prepreg. To improve the toughness of epoxy resin, a large number of toughening particles need to be blended, which causes the resin viscosity to increase sharply, seriously affecting the wettability of the prepreg and thus reducing the molding quality of the composite material. To solve the above problems and achieve a balance between prepreg wettability and high damage tolerance, a gradient prepreg preparation method of "first impregnation, then coating" is needed to simultaneously achieve high microwave transmission and high toughness of prepregs for automated fiber placement. Summary of the Invention
[0004] The purpose of this invention is to propose a high-toughness, low-dielectric epoxy resin prepreg for automated fiber placement and its preparation method, so as to solve the problem that existing epoxy resin prepregs are difficult to balance low dielectric wave transmission, fiber wettability, high damage tolerance and automated fiber placement processability, and achieve the effects of low dielectric, high molding quality, high damage tolerance and long operating life.
[0005] The objective of this invention is mainly achieved through the following technical solutions.
[0006] A high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement includes unidirectional reinforcing fibers, a low-dielectric resin layer for impregnation, and a low-dielectric, high-toughness resin layer for coating. The areal density of the unidirectional reinforcing fiber is 30-400 g / m². 2 The areal density of the low-dielectric resin layer used for impregnation is 20~300 g / m², and the areal density of the low-dielectric high-toughness resin layer used for coating is 5~100 g / m². 2 ; The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement is a hot-melt prepreg with a multi-layer structure. The low-dielectric resin layer for impregnation is impregnated in the unidirectional reinforcing fiber, and the low-dielectric, high-toughness resin layer for coating is coated on the surface of the unidirectional reinforcing fiber after being impregnated by the low-dielectric resin layer for impregnation.
[0007] Furthermore, the unidirectional reinforcing fiber is one or more of the following: E-type glass fiber, S-type glass fiber, quartz fiber, aramid fiber, liquid crystal fiber, polyimide fiber, basalt fiber, polyethylene fiber or its fabric, PBO fiber or its fabric, and plant fiber.
[0008] Furthermore, the impregnation low-dielectric resin layer is formed of the impregnation low-dielectric resin, which, by weight, comprises 30-60 parts of low-dielectric epoxy resin copolymer component, 20-30 parts of low-viscosity high-toughness epoxy resin component, 10-25 parts of latent curing agent component, and 5-20 parts of interface reinforcement component.
[0009] Furthermore, the low-dielectric high-toughness resin layer for coating is formed from a low-dielectric high-toughness resin for coating. By weight, the low-dielectric high-toughness resin for coating comprises 30-70 parts of a low-dielectric epoxy resin copolymer component, 10-25 parts of a low-dielectric organic toughening particle component, and 10-25 parts of a low-dielectric inorganic rigid particle component.
[0010] Further, the low-dielectric epoxy resin copolymer component comprises a low-dielectric epoxy resin monomer and a low-dielectric copolymer component; the low-dielectric epoxy resin monomer is one or more of fluorinated epoxy resin, dicyclopentadiene type epoxy resin, biphenyl type epoxy resin, cage-type silsesquioxane modified epoxy resin, alicyclic epoxy resin, and organosilicon modified epoxy resin, and the epoxy equivalent of the low-dielectric epoxy resin monomer is 100-300 g / eq; the low-dielectric copolymer component is one or more of cyanate ester, hydrocarbon resin, and benzocyclobutene resin.
[0011] Further, the cyanate ester is one or more of bisphenol A cyanate ester, bisphenol E cyanate ester, bisphenol M cyanate ester, bisphenol F cyanate ester, dicyclopentadiene bisphenol cyanate ester, and phenolic cyanate ester.
[0012] Furthermore, the benzocyclobutene resin is one or more of monobenzocyclobutene, dibenzocyclobutene, or polybenzocyclobutene containing an imide structure, a fluorine structure, a trifluoromethyl structure, a siloxane structure, an aromatic ether structure, a saturated alkane structure, an unsaturated alkane structure, an amide structure, or a carbonyl structure.
[0013] Further, the hydrocarbon resin includes one or more of cyclic olefin copolymers, linear olefin copolymers, cyclic olefin homopolymers, and linear olefin homopolymers; the side chains of the hydrocarbon resin have reactive groups capable of reacting with epoxy resin, the reactive groups being one or more of hydroxyl, vinyl, amino, and anhydride groups, and the molecular weight of the hydrocarbon resin is 500-50000.
[0014] Furthermore, the low-viscosity, high-toughness epoxy resin component is one or more of the following: bisphenol A type polyether epoxy resin, bisphenol F type polyether epoxy resin, bisphenol AF type polyether epoxy resin, triethoxysilane type polyether epoxy resin, glycidyl ether epoxy resin, polyurethane epoxy resin, and hyperbranched polyester epoxy resin; the room temperature viscosity of the low-viscosity, high-toughness epoxy resin is 0.01-10 Pa·s.
[0015] Further, the latent curing agent component comprises one or more of the following: dicyandiamide, vinyltriamine, ethylenediamine, methylenedicyclohexaneamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diallyltriamine, dimethylaminopropylamine, m-phenylenediamine, hexahydropyridine, dibenzylamino ether, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, trimellitic anhydride glycerol, polyazelite anhydride, methylhexahydrophthalic anhydride, polysaccharide anhydride, diphenyl ether tetracarboxylic dianhydride, cyclopentadiene tetracarboxylic dianhydride, and linear phenolic resin.
[0016] Furthermore, the interface enhancement component is a polyalkylsilane resin monomer, which includes one or more of aminopropyltriethoxysilane, (2,3-epoxypropoxy)propyltrimethoxysilane, (methacryloyl)propyltrimethoxysilane, bismaleimide-type triethoxysilane, and cyanate ester-type triethoxysilane.
[0017] Furthermore, the low-dielectric organic toughening particle component is an organic hollow microsphere, which includes one or more of thermoplastic polyimide hollow microspheres, polyphenylene ether hollow microspheres, polyetheretherketone hollow microspheres, polyaryletherketone hollow microspheres, polyamide hollow microspheres, polyarylether sulfone hollow microspheres, polyethersulfone hollow microspheres, and polyphenylene sulfide hollow microspheres, and the average particle size of the organic hollow microspheres is 1-20 μm.
[0018] Furthermore, the low-dielectric inorganic rigid particle component is an inorganic hollow microsphere, which includes one or more of the following: silica hollow microspheres, alumina hollow microspheres, titanium dioxide hollow microspheres, zinc oxide hollow microspheres, magnesium oxide hollow microspheres, aluminum hydroxide hollow microspheres, magnesium hydroxide hollow microspheres, ceramic hollow microspheres, barium titanate hollow microspheres, sodium titanate hollow microspheres, boron nitride hollow microspheres, and carbon nanotube modified hollow microspheres. The average particle size of the inorganic hollow microspheres is 100 nm to 20 μm.
[0019] Furthermore, the average particle size of the low-dielectric organic toughening particle component is different from that of the low-dielectric inorganic rigid particle component.
[0020] A method for preparing a high-toughness, low-dielectric epoxy resin prepreg for automated fiber placement includes the following steps: 1) Preparation of low dielectric resin for impregnation: Mix low dielectric epoxy resin copolymer component, low viscosity high toughness epoxy resin component, interface reinforcement component and latent curing agent component to obtain low dielectric resin for impregnation. 2) Preparation of low-dielectric high-toughness resin for coating: Mix low-dielectric epoxy resin copolymer component, low-dielectric organic toughening particle component and low-dielectric inorganic rigid particle component to obtain low-dielectric high-toughness resin for coating. 3) Preparation of resin film: The low dielectric resin for impregnation is coated to form a low dielectric resin film for impregnation, and the low dielectric high toughness resin for coating is coated to form a low dielectric high toughness resin film for coating. 4) Gradient composite: The impregnation low-dielectric resin film is composited with unidirectional reinforcing fibers, so that the impregnation low-dielectric resin penetrates into the unidirectional reinforcing fibers to obtain a prepreg intermediate; the prepreg intermediate is composited with the coating low-dielectric high-toughness resin film, so that the coating low-dielectric high-toughness resin is coated on the surface of the prepreg intermediate to obtain a wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg. 5) Preparation of fixed-width prepreg bundles: The wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg is cut to obtain fixed-width prepreg bundles.
[0021] Further, in step 1), 30-50 parts of the low-dielectric epoxy resin copolymer component are heated to melt within a temperature range of 80-110°C, 20-30 parts of the low-viscosity high-toughness epoxy resin component and 5-10 parts of the interface reinforcement component are added, and the mixture is stirred until a homogeneous phase is formed. Then, the temperature is lowered to 50-80°C, 10-25 parts of the latent curing agent component are added, and the mixture is stirred evenly and kept at a constant temperature for 2-5 hours to obtain the low-dielectric resin for impregnation.
[0022] Further, in step 1), the viscosity of the low dielectric resin for impregnation at 70-80°C is monitored using a rotational viscometer, and the temperature is stopped and the material is discharged when the resin viscosity is 7-30 Pa·s.
[0023] Further, in step 2), 30-60 parts of the low-dielectric epoxy resin copolymer component are heated to melt within a temperature range of 80-110°C, and 10-25 parts of the low-dielectric organic toughening particle component with an average particle size of 1-20 μm and 10-25 parts of the low-dielectric inorganic rigid particle component with a particle size of 100 nm-20 μm are added. The mixture is stirred until a homogeneous phase is formed to obtain the low-dielectric high-toughness resin for coating.
[0024] Further, in step 3), a hot-melt prepreg coating machine is used. Within a temperature range of 70-80℃, a sequential coating method is employed. The gap between the coating rollers is adjusted to 0.05-0.25mm, and the roller speed difference percentage is adjusted to 10%-40%. The low-dielectric resin for impregnation is coated to a surface density of 20-300 g / m². 2 The impregnation uses a low-dielectric resin film with a film accuracy of ±5 g / m. 2 .
[0025] Further, in step 3), a hot-melt prepreg coating machine is used. Within a temperature range of 80-110℃, a sequential coating method is employed. The gap between the coating rollers is adjusted to 0.05-0.10mm, and the roller speed difference percentage is adjusted to 10%-20%. The low-dielectric, high-toughness resin used for coating is then coated to a surface density of 5-100 g / m². 2 The coating uses a low-dielectric, high-toughness resin film with a film precision of ±5 g / m. 2 .
[0026] Further, in step 4), the low-dielectric resin film for impregnation and the film with an areal density of 30-400 g / m² are used. 2 The unidirectional reinforcing fibers are compounded by the first three pressing rollers, the gap between the first three pressing rollers is 0.05-0.15mm, and the pressing temperature is 80-90℃.
[0027] Further, in step 4), the prepreg intermediate and the low dielectric high toughness resin film for coating are compounded by three subsequent pressing rollers. The gap between the three subsequent pressing rollers is 0.1-0.3 mm, and the pressing temperature is 90-120℃.
[0028] Furthermore, in step 4), the pressing pressure when the impregnating low-dielectric resin film is compounded with the unidirectional reinforcing fiber is greater than the pressing pressure when the prepreg intermediate is compounded with the coating low-dielectric high-toughness resin film.
[0029] Further, in step 5), the wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg is first-stage coarsely cut to obtain a prepreg narrow strip with a width of 25-200mm. Then, the prepreg narrow strip is second-stage finely cut and prepared into fixed-width prepreg bundles with widths of 3.175mm, 6.35mm, or 12.7mm by a precision slitting machine and winding equipment.
[0030] Compared with the prior art, the present invention has the following advantages: (1) The present invention provides an epoxy resin prepreg that has low dielectric properties, high damage tolerance and excellent automatic fiber placement process.
[0031] (2) This invention provides a method for simultaneously achieving low dielectric functionality and high damage tolerance of prepreg. The specific method is as follows: through gradient composite technology, a multi-layer structure is formed of a high-toughness low-dielectric epoxy resin prepreg for automatic fiber placement, which includes unidirectional reinforcing fibers, a low-dielectric resin layer for impregnation, and a low-dielectric high-toughness resin layer for coating, from the inside out; firstly, a low-viscosity low-dielectric resin film is used to fully impregnate the unidirectional reinforcing fibers, and the low-viscosity low-dielectric resin matrix is promoted to enter the interior of the unidirectional reinforcing fiber bundle through higher composite pressure and composite temperature, thereby significantly improving the low dielectric functionality of the prepreg and the internal quality of the molded part; then, a low-dielectric resin film with high toughening agent content is coated on the surface of the impregnated prepreg, and the high-toughening agent content low-dielectric resin is mainly distributed on the surface of the prepreg and the interlayer area through lower composite pressure and composite temperature, which significantly improves the interlayer toughening agent content of the prepreg and reduces the breakage rate of hollow microspheres, thereby improving the damage tolerance of the prepreg. Using this technology, a gradient functional distribution of prepreg can be achieved, thereby simultaneously realizing the integration of prepreg structure and function.
[0032] (3) The present invention provides a method for extending the operating life of automated fiber placement prepreg to meet the automatic placement and molding cycle of large-size primary / secondary load-bearing structures. The specific method is as follows: for the impregnation resin, a latent curing agent, such as a dicyandiamide curing agent, is introduced so that the resin is cured only at high temperature, thereby extending the room temperature storage period of the prepreg; for the coating resin, no curing agent is introduced, thereby extending the surface tack decay time of the prepreg, so that the operating life of the automated fiber placement prepreg is not less than 30 days.
[0033] (4) The present invention provides a method for optimizing the dielectric properties and processability of impregnation resin, so as to improve the resin / fiber impregnation, reduce the dielectric constant of composite material and improve the mechanical properties of composite material. The specific method is as follows: Monomers capable of cross-linking with epoxy resin, such as cyanate esters, hydrocarbon resins, and benzocyclobutene resins, are introduced to form a low-dielectric epoxy resin copolymer component. Interface reinforcement components are introduced, such as resin monomers containing triethoxysilane structures. These monomers bind to oxygen-containing functional groups of the transparent fiber at one end and form a cross-linked structure with the resin at the other end, achieving chemical bonding between the resin and fiber. This enhances the interfacial bonding strength between the resin and fiber, thereby improving the mechanical properties of the composite material. Existing technologies commonly use the introduction of soluble toughening agents to improve the intrinsic toughness of the resin, thereby improving the mechanical properties of the composite material. However, soluble toughening agents significantly increase resin viscosity after dissolving in the resin matrix, thus reducing resin / fiber wettability. Therefore, this invention introduces a low-viscosity, high-toughness epoxy resin component, such as polyether epoxy resin, to increase the intrinsic toughness of the resin and improve the wetting ability of the low-dielectric resin for impregnation of unidirectional reinforcing fibers through its low-viscosity characteristics. Meanwhile, the resin viscosity is precisely controlled by adjusting the degree of resin prepolymerization, so as to balance the resin wettability, fiber laying process and internal quality of the prepreg.
[0034] (5) This invention provides a method for optimizing the dielectric properties and toughness of resins used for coating, so as to reduce the dielectric constant of composite materials while improving the damage tolerance of composite materials. The specific method is as follows: by introducing hollow microspheres, and then introducing a low-dielectric air phase, the dielectric constant of composite materials is reduced; at the same time, organic hollow microspheres and inorganic hollow microspheres of different particle sizes are compounded, so that the organic hollow microspheres play a toughening role and the inorganic hollow microspheres play a rigid support role, thereby simultaneously improving the modulus and toughness of composite materials, and by coating, the enrichment degree of toughening particles on the surface of prepreg and the interlayer region is increased, thereby improving the damage tolerance of composite materials. Detailed Implementation
[0035] To make the various technical features, advantages, or effects of the present invention more apparent and understandable, detailed descriptions are provided below through embodiments.
[0036] Example 1 Step 1: Preparation of low-dielectric resin for impregnation: At 95°C, 45 parts of low-dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt. 25 parts of bisphenol A type polyether epoxy resin with a room temperature viscosity of 5 Pa·s and 10 parts of aminopropyltriethoxysilane were added and stirred until a homogeneous phase was formed. The temperature was then lowered to 65°C, and 15 parts of dicyandiamide curing agent were added. After stirring evenly, the temperature was kept constant for 3 hours. The resin viscosity at 75°C was monitored using a rotational viscometer. When the viscosity reached 15 Pa·s, the temperature was kept constant and the material was discharged.
[0037] Step 2: Preparation of low-dielectric, high-toughness resin for coating: 50 parts of low dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt within a temperature range of 95℃. 15 parts of hollow thermoplastic polyimide microspheres with an average particle size of 10 μm and 15 parts of hollow silica with an average particle size of 5 μm were added and stirred until a homogeneous phase was formed.
[0038] Step 3: Preparation of resin film: Using a hot-melt prepreg coating machine at 75℃, employing a sequential coating method, adjust the coating roller gap to 0.15mm and the coating roller speed difference percentage to 25%, and apply 150g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0039] Using a hot-melt prepreg coating machine at 95℃, employing a sequential coating method, adjust the coating roller gap to 0.075mm and the coating roller speed difference percentage to 15%, and apply 50g / m² of low-dielectric resin for impregnation. 2 The resin film has a precision of ±5 g / m2.
[0040] Step 4: Gradient Composition: Impregnate with low dielectric resin film and 235g / 2 Unidirectional quartz fibers are laminated using three pressing rollers, allowing resin to permeate the unidirectional reinforcing fibers. The gap between the first three pressing rollers is 0.10 mm, and the pressing temperature is 85°C. Then, the prepreg is laminated with a resin film for coating using three pressing rollers, coating the surface of the prepreg with a high-modulus, high-toughness component. The gap between the last three pressing rollers is 0.20 mm, and the pressing temperature is 105°C. This process ultimately yields a wide-width, automatically laid-out, high-toughness, low-dielectric epoxy resin prepreg.
[0041] Step 5: Prepare prepreg bundles of a fixed width: The wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg prepared by the hot melt method is first-stage coarsely cut to obtain a 100mm prepreg narrow strip. Then, the prepreg narrow strip is second-stage finely cut, and a 6.35mm fixed-width prepreg bundle is prepared by a precision slitting machine and winding equipment.
[0042] The surface tack of the obtained high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement was tested. The data are detailed in Table 1. The surface tack of the prepreg is suitable for automatic fiber placement process. At the same time, the surface tack of the prepreg is suitable after 30 days, and the operating life is greater than 30 days.
[0043] The obtained high-toughness, low-dielectric epoxy resin prepreg for automated fiber placement was used, and an autoclave molding process was employed. The curing procedure was 130℃ / 1h + 180℃ / 2h. The properties of the laminate are shown in Table 1. The dielectric constant (2-18GHz) of the laminate is less than 3.20, and the CAI value is greater than 290MPa. It possesses excellent low-dielectric functionality, high damage tolerance, and scalability for automated fiber placement.
[0044] Example 2 Step 1: Preparation of low-dielectric resin for impregnation: At 80℃, 30 parts of low-dielectric epoxy resin copolymer (containing dicyclopentadiene-type epoxy resin with an epoxy equivalent of 100 g / eq and fluorocyanate) were heated to melt. 20 parts of hyperbranched polyester epoxy resin with a room temperature viscosity of 0.01 Pa·s and 5 parts of cyanate-type triethoxysilane were added and stirred until a homogeneous phase was formed. The temperature was then lowered to 50℃, and 10 parts of 2-methylimidazolium curing agent were added. After stirring evenly, the temperature was kept constant for 2 hours. The viscosity of the resin at 70℃ was monitored using a rotational viscometer. When the viscosity reached 7 Pa·s, the temperature was kept constant and the material was discharged.
[0045] Step 2: Preparation of low-dielectric, high-toughness resin for coating: 30 parts of low dielectric epoxy resin copolymer (containing dicyclopentadiene-type epoxy resin with an epoxy equivalent of 100 g / eq and fluorocyanate) were heated to melt within a temperature range of 80℃. 10 parts of hollow polyphenylene ether microspheres with an average particle size of 1 μm and 10 parts of hollow alumina microspheres with an average particle size of 100 nm were added and stirred until a homogeneous phase was formed.
[0046] Step 3: Preparation of resin film: Using a hot-melt prepreg coating machine at 70℃, employing a sequential coating method, adjust the coating roller gap to 0.05mm and the coating roller speed difference percentage to 10%, and apply 20g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0047] Using a hot-melt prepreg coating machine at 80℃, a sequential coating method is employed. The gap between the coating rollers is adjusted to 0.05mm, and the roller speed difference percentage is adjusted to 10%. The low-dielectric resin for impregnation is applied at a concentration of 5g / m². 2 The resin film has a film precision of ±5 g / m 2 .
[0048] Step 4: Gradient Composition: Impregnate with low dielectric resin film and 30g / m 2Unidirectional quartz fibers are laminated using three pressing rollers, allowing resin to permeate the unidirectional reinforcing fibers. The gap between the first three pressing rollers is 0.05 mm, and the pressing temperature is 80°C. Then, the prepreg is laminated with a coating resin film using three subsequent pressing rollers, coating the surface of the prepreg with a high-modulus, high-toughness component. The gap between the subsequent three pressing rollers is 0.10 mm, and the pressing temperature is 90°C. This process ultimately yields a wide-width, automatically laid-out, high-toughness, low-dielectric epoxy resin prepreg.
[0049] Step 5: Prepare prepreg bundles of a fixed width: The wide-width, high-toughness, low-dielectric epoxy resin prepreg prepared by the hot-melt method is first-stage coarsely cut to obtain a 25mm prepreg narrow strip. Then, the prepreg narrow strip is second-stage finely cut, and the prepreg bundle with a fixed width of 3.175mm is prepared by a precision slitting machine and a winding device.
[0050] The surface tack of the obtained high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement was tested. The data are detailed in Table 1. The surface tack of the prepreg is suitable for automatic fiber placement process. At the same time, the surface tack of the prepreg is suitable after 30 days, and the operating life is greater than 30 days.
[0051] The obtained high-toughness, low-dielectric epoxy resin prepreg for automated fiber placement was used, and an autoclave molding process was employed. The curing procedure was 130℃ / 1h + 180℃ / 2h. The properties of the laminate are shown in Table 1. The dielectric constant (2-18GHz) of the laminate is less than 3.20, and the CAI value is greater than 290MPa. It possesses excellent low-dielectric functionality, high damage tolerance, and scalability for automated fiber placement.
[0052] Example 3 Step 1: Preparation of low-dielectric resin for impregnation: At 110℃, 60 parts of low-dielectric epoxy resin copolymer (containing cage-type silsesquioxane modified epoxy resin with an epoxy equivalent of 300 g / eq and bisphenol A cyanate) were heated to melt. 30 parts of bisphenol AF type polyether epoxy resin with a room temperature viscosity of 10 Pa·s and 20 parts of (2,3-epoxypropoxy)propyltrimethoxysilane were added and stirred until a homogeneous phase was formed. The temperature was then lowered to 80℃, and 25 parts of 1-cyanoethyl-2-ethyl-4-methylimidazolium curing agent were added. After stirring evenly, the temperature was kept constant for 5 hours. The viscosity of the resin at 80℃ was monitored using a rotational viscometer. When the viscosity reached 30 Pa·s, the temperature was kept constant and the material was discharged.
[0053] Step 2: Preparation of low-dielectric, high-toughness resin for coating: 70 parts of low dielectric epoxy resin copolymer (containing cage-type silsesquioxane modified epoxy resin with an epoxy equivalent of 300 g / eq and bisphenol A cyanate) were heated to melt within a temperature range of 110℃. 25 parts of hollow polyarylene ether sulfone microspheres with an average particle size of 20 μm and 25 parts of hollow aluminum hydroxide microspheres with an average particle size of 20 μm were added, and the mixture was stirred until a homogeneous phase was formed.
[0054] Step 3: Preparation of resin film: Using a hot-melt prepreg coating machine at 80℃, employing a sequential coating method, adjust the coating roller gap to 0.25mm and the coating roller speed difference percentage to 40%, and apply 300g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0055] Using a hot-melt prepreg coating machine at 110℃, a sequential coating method is employed. The gap between the coating rollers is adjusted to 0.10mm, and the roller speed difference percentage is adjusted to 20%. The low-dielectric resin for impregnation is coated at a concentration of 100g / m². 2 The resin film has a film precision of ±5 g / m 2 .
[0056] Step 4: Gradient Composition: Impregnated with low-dielectric resin film and 400g / m 2 Unidirectional quartz fibers are laminated using three pressing rollers, allowing resin to permeate the unidirectional reinforcing fibers. The gap between the first three pressing rollers is 0.15 mm, and the pressing temperature is 90°C. Then, the prepreg is laminated with a resin film for coating using three pressing rollers, coating the surface of the prepreg with a high-modulus, high-toughness component. The gap between the last three pressing rollers is 0.30 mm, and the pressing temperature is 120°C. This process ultimately yields a wide-width, automatically laid-out, high-toughness, low-dielectric epoxy resin prepreg.
[0057] Step 5: Prepare prepreg bundles of a fixed width: The wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg prepared by the hot melt method is first-stage coarsely cut to obtain a 200mm prepreg narrow strip. Then, the prepreg narrow strip is second-stage finely cut, and a 12.7mm fixed-width prepreg bundle is prepared by a precision slitting machine and winding equipment.
[0058] The surface tack of the obtained high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement was tested. The data are detailed in Table 1. The surface tack of the prepreg is suitable for automatic fiber placement process. At the same time, the surface tack of the prepreg is suitable after 30 days, and the operating life is greater than 30 days.
[0059] The obtained high-toughness, low-dielectric epoxy resin prepreg for automated fiber placement was used, and an autoclave molding process was employed. The curing procedure was 130℃ / 1h + 180℃ / 2h. The properties of the laminate are shown in Table 1. The dielectric constant (2-18GHz) of the laminate is less than 3.20, and the CAI value is greater than 290MPa. It possesses excellent low-dielectric functionality, high damage tolerance, and scalability for automated fiber placement.
[0060] Comparative Example 1 Step 1: Preparation of low-dielectric resin for impregnation: At 95°C, 45 parts of low-dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt. 25 parts of bisphenol A type polyether epoxy resin with a room temperature viscosity of 5 Pa·s and 10 parts of aminopropyltriethoxysilane were added and stirred until a homogeneous phase was formed. The temperature was then lowered to 65°C, and 15 parts of dicyandiamide curing agent were added. After stirring evenly, the temperature was kept constant for 3 hours. The resin viscosity at 75°C was monitored using a rotational viscometer. When the viscosity reached 15 Pa·s, the temperature was kept constant and the material was discharged.
[0061] Step 2: Preparation of low-dielectric, high-toughness resin for coating: 50 parts of low dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt within a temperature range of 95℃. 15 parts of hollow thermoplastic polyimide microspheres with an average particle size of 10 μm and 15 parts of hollow silica with an average particle size of 5 μm were added and stirred until a homogeneous phase was formed. Then, 20 parts of diaminodiphenyl sulfone curing agent were added and dispersed until a homogeneous phase was formed before discharging.
[0062] Step 3: Preparation of resin film: Using a hot-melt prepreg coating machine at 75℃, employing a sequential coating method, adjust the coating roller gap to 0.15mm and the coating roller speed difference percentage to 25%, and apply 150g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0063] Using a hot-melt prepreg coating machine at 95℃, employing a sequential coating method, adjust the coating roller gap to 0.075mm and the coating roller speed difference percentage to 15%, and apply 50g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0064] Step 4: Gradient Composition: Impregnated with low dielectric resin film and 235g / m 2Unidirectional quartz fibers are laminated using three pressing rollers, allowing resin to permeate the unidirectional reinforcing fibers. The gap between the first three pressing rollers is 0.10 mm, and the pressing temperature is 85°C. Then, the prepreg is laminated with a resin film for coating using three pressing rollers, coating the surface of the prepreg with a high-modulus, high-toughness component. The gap between the last three pressing rollers is 0.20 mm, and the pressing temperature is 105°C. This process ultimately yields a wide-width, automatically laid-out, high-toughness, low-dielectric epoxy resin prepreg.
[0065] Step 5: Prepare prepreg bundles of a fixed width: The wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg prepared by the hot melt method is first-stage coarsely cut to obtain a 100mm prepreg narrow strip. Then, the prepreg narrow strip is second-stage finely cut, and a 6.35mm fixed-width prepreg bundle is prepared by a precision slitting machine and winding equipment.
[0066] The surface tack of the obtained high-toughness, low-dielectric epoxy resin prepreg for automated fiber placement was tested, and the data are detailed in Table 1. Compared to Example 1, the low-dielectric, high-toughness resin for coating in Comparative Example 1 introduced a curing agent component, resulting in a significant decrease in the surface tack of the prepreg, making it unsuitable for automated fiber placement and limiting its operational life to less than 30 days. Therefore, it can be concluded that by not introducing a curing agent into the surface resin of the automated fiber placement prepreg, the resin crosslinking reaction can be delayed, the surface tack decay time of the prepreg can be extended, and thus the operational life of the prepreg can be significantly improved.
[0067] Comparative Example 2 Step 1: Preparation of low-dielectric resin for impregnation: At 95°C, 45 parts of low-dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt. 25 parts of bisphenol A type polyether epoxy resin with a room temperature viscosity of 5 Pa·s and 10 parts of aminopropyltriethoxysilane were added and stirred until a homogeneous phase was formed. The temperature was then lowered to 65°C, and 15 parts of dicyandiamide curing agent were added. After stirring evenly, the temperature was kept constant for 3 hours. The resin viscosity at 75°C was monitored using a rotational viscometer. When the viscosity reached 15 Pa·s, the temperature was kept constant and the material was discharged.
[0068] Step 2: Preparation of low-dielectric, high-toughness resin for coating: 50 parts of low dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt within a temperature range of 95℃. 15 parts of solid thermoplastic polyimide microspheres with an average particle size of 10 μm and 15 parts of solid silica with an average particle size of 5 μm were added and stirred until a homogeneous phase was formed.
[0069] Step 3: Preparation of resin film: Using a hot-melt prepreg coating machine at 75℃, employing a sequential coating method, adjust the coating roller gap to 0.15mm and the coating roller speed difference percentage to 25%, and apply 150g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0070] Using a hot-melt prepreg coating machine at 95℃, employing a sequential coating method, adjust the coating roller gap to 0.075mm and the coating roller speed difference percentage to 15%, and apply 50g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0071] Step 4: Gradient Composition: Impregnated with low dielectric resin film and 235g / m 2 Unidirectional quartz fibers are laminated using three pressing rollers, allowing resin to permeate the unidirectional reinforcing fibers. The gap between the first three pressing rollers is 0.10 mm, and the pressing temperature is 85°C. Then, the prepreg is laminated with a resin film for coating using three pressing rollers, coating the surface of the prepreg with a high-modulus, high-toughness component. The gap between the last three pressing rollers is 0.20 mm, and the pressing temperature is 105°C. This process ultimately yields a wide-width, automatically laid-out, high-toughness, low-dielectric epoxy resin prepreg.
[0072] Step 5: Prepare prepreg bundles of a fixed width: The wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg prepared by the hot melt method is first-stage coarsely cut to obtain a 100mm prepreg narrow strip. Then, the prepreg narrow strip is second-stage finely cut, and a 6.35mm fixed-width prepreg bundle is prepared by a precision slitting machine and winding equipment.
[0073] The obtained high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement was used in an autoclave molding process with a curing procedure of 130℃ / 1h + 180℃ / 2h. The properties of the laminate are shown in Table 1. Compared to Example 1, the organic toughening particles and inorganic rigid particles in the comparative example were both solid particles, resulting in a dielectric constant (2-18GHz) greater than 3.20 for the composite material, indicating poor dielectric properties. This demonstrates that adding hollow particles can introduce a high proportion of low-dielectric phase, forming a "physical dilution," thereby significantly reducing the dielectric constant of the composite material.
[0074] Comparative Example 3 Step 1: Preparation of low-dielectric resin for impregnation: At 95°C, 45 parts of low-dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt. 25 parts of bisphenol A type polyether epoxy resin with a room temperature viscosity of 5 Pa·s and 10 parts of aminopropyltriethoxysilane were added and stirred until a homogeneous phase was formed. The temperature was then lowered to 65°C, and 15 parts of dicyandiamide curing agent were added. After stirring evenly, the temperature was kept constant for 3 hours. The resin viscosity at 75°C was monitored using a rotational viscometer. When the viscosity reached 15 Pa·s, the temperature was kept constant and the material was discharged.
[0075] Step 2: Preparation of low-dielectric, high-toughness resin for coating: 50 parts of low dielectric epoxy resin copolymer (containing fluorinated epoxy resin with an epoxy equivalent of 200 g / eq and dicyclopentadiene cyanate) were heated to melt within a temperature range of 95℃, and 30 parts of hollow thermoplastic polyimide microspheres with an average particle size of 10 μm were added and stirred until a homogeneous phase was formed.
[0076] Step 3: Preparation of resin film: Using a hot-melt prepreg coating machine at 75℃, employing a sequential coating method, adjust the coating roller gap to 0.15mm and the coating roller speed difference percentage to 25%, and apply 150g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0077] Using a hot-melt prepreg coating machine at 95℃, employing a sequential coating method, adjust the coating roller gap to 0.075mm and the coating roller speed difference percentage to 15%, and apply 50g / m² of low-dielectric resin for impregnation. 2 The resin film has a film precision of ±5 g / m 2 .
[0078] Step 4: Gradient Composition: Impregnated with low dielectric resin film and 235g / m 2 Unidirectional quartz fibers are laminated using three pressing rollers, allowing resin to permeate the unidirectional reinforcing fibers. The gap between the first three pressing rollers is 0.10 mm, and the pressing temperature is 85°C. Then, the prepreg is laminated with a resin film for coating using three pressing rollers, coating the surface of the prepreg with a high-modulus, high-toughness component. The gap between the last three pressing rollers is 0.20 mm, and the pressing temperature is 105°C. This process ultimately yields a wide-width, automatically laid-out, high-toughness, low-dielectric epoxy resin prepreg.
[0079] Step 5: Prepare prepreg bundles of a fixed width: The wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg prepared by the hot melt method is first-stage coarsely cut to obtain a 100mm prepreg narrow strip. Then, the prepreg narrow strip is second-stage finely cut, and a 6.35mm fixed-width prepreg bundle is prepared by a precision slitting machine and winding equipment.
[0080] The obtained high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement was used in an autoclave molding process with a curing procedure of 130℃ / 1h + 180℃ / 2h. The properties of the laminate are shown in Table 1. Compared to Example 1, the comparative example only introduced organic hollow toughening particles, resulting in a composite material CAI value significantly lower than 290MPa and poor damage tolerance. This indicates that a combination of organic hollow toughening particles and inorganic rigid toughening particles is necessary to simultaneously balance the stiffness and toughness of the composite material, thereby improving its damage tolerance.
[0081] Table 1. Comprehensive Properties of Low-Dielectric, High-Heat-Resistant Epoxy Resin for Wave-Transparent Automatic Fiber Placement Prepreg As shown in Table 1, the dielectric constant of the laminates of the high-toughness, low-dielectric epoxy resin prepregs for automated fiber placement obtained in Examples 1 to 3 is 3.10-3.20 in the range of 2-18 GHz, the compressive strength of the laminates after impact is 301-310 MPa, the initial surface tack of the prepreg is 20-25 N, and the surface tack remains at 14-16 N after 30 days. These results indicate that the prepregs obtained in this invention can simultaneously meet the requirements of low dielectric functionality, high damage tolerance, and automated fiber placement processability, and have an operating life of no less than 30 days.
[0082] Compared to Comparative Example 1, Example 1 showed little difference in the dielectric constant and post-impact compressive strength of the laminates. However, in Comparative Example 1, after introducing a curing agent into the low-dielectric, high-toughness resin for coating, the surface tack of the prepreg decreased from 15N in Example 1 to 2N after 30 days, indicating a significant decrease in surface tack, which was insufficient to meet the long-term operating life requirements of the automated fiber placement process. This demonstrates that by not introducing a curing agent into the low-dielectric, high-toughness resin for coating, the crosslinking reaction of the resin on the surface of the prepreg can be delayed, reducing the rate of surface tack decay and thus significantly extending the operating life of the prepreg for automated fiber placement.
[0083] Compared to Comparative Example 2, Example 2, by replacing the organic and inorganic hollow microspheres in the coating resin with corresponding solid particles, showed an increase in the dielectric constant of the laminate from 3.15-3.20 in Example 1 to 3.35-3.40. Although the compressive strength after impact remained at 306 MPa, the low dielectric properties significantly decreased. This demonstrates that introducing hollow particles into the low dielectric, high toughness resin for coating can introduce a low dielectric air phase into the composite material, reducing the overall dielectric constant of the composite material through physical dilution, thereby improving the low dielectric functionality of the prepreg.
[0084] Compared to Comparative Example 3, Example 3 only introduced organic hollow toughening particles into the coating resin without compounding inorganic hollow rigid particles. The dielectric constant of its laminate was essentially the same as that of Example 1, but the post-impact compressive strength decreased from 305 MPa in Example 1 to 250 MPa, indicating a significant reduction in damage tolerance. This demonstrates that using only organic hollow toughening particles is insufficient to simultaneously achieve both rigid support and interlaminar toughening effects in composite materials. However, compounding organic hollow toughening particles with inorganic hollow rigid particles can simultaneously improve the modulus, toughness, and post-impact compressive strength of the composite material while maintaining low dielectric properties.
[0085] In summary, Examples 1 to 3 achieved a gradient functional distribution between the low-dielectric resin impregnation layer and the low-dielectric high-toughness coating layer by fully impregnating the unidirectional reinforcing fibers with a low-viscosity, low-dielectric resin film containing organic hollow toughening particles and inorganic hollow rigid particles on the surface of the prepreg. This structure improves the resin / fiber impregnation quality and the internal quality of the part, increases the interlayer toughening agent content, and reduces the dielectric constant and surface viscosity decay rate, thereby achieving a synergistic improvement in the low-dielectric functionality, high damage tolerance, and automated fiber placement processability of the prepreg.
[0086] Although the present invention has been disclosed above with reference to embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention should be covered within the protection scope of the present invention, which is defined by the claims.
Claims
1. A high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement, characterized in that, It includes unidirectional reinforcing fibers, a low-dielectric resin layer for impregnation, and a low-dielectric, high-toughness resin layer for coating; The areal density of the unidirectional reinforcing fiber is 30-400 g / m². 2 The areal density of the low-dielectric resin layer used for impregnation is 20-300 g / m³. 2 The areal density of the low-dielectric, high-toughness resin layer used for coating is 5-100 g / m³. 2 ; The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement is a hot-melt prepreg with a multi-layer structure. The low-dielectric resin layer for impregnation is impregnated in the unidirectional reinforcing fiber, and the low-dielectric, high-toughness resin layer for coating is coated on the surface of the unidirectional reinforcing fiber after being impregnated by the low-dielectric resin layer for impregnation.
2. The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement as described in claim 1, characterized in that, The unidirectional reinforcing fiber is one or more of the following: E-type glass fiber, S-type glass fiber, quartz fiber, aramid fiber, liquid crystal fiber, polyimide fiber, basalt fiber, polyethylene fiber or its fabric, PBO fiber or its fabric, and plant fiber.
3. The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement as described in claim 1, characterized in that, The impregnation low-dielectric resin layer is formed from the impregnation low-dielectric resin, which, by weight, comprises 30-60 parts of low-dielectric epoxy resin copolymer component, 20-30 parts of low-viscosity high-toughness epoxy resin component, 10-25 parts of latent curing agent component, and 5-20 parts of interface reinforcement component.
4. The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement as described in claim 3, characterized in that, The low-viscosity, high-toughness epoxy resin component is one or more of the following: bisphenol A type polyether epoxy resin, bisphenol F type polyether epoxy resin, bisphenol AF type polyether epoxy resin, triethoxysilane type polyether epoxy resin, glycidyl ether epoxy resin, polyurethane epoxy resin, and hyperbranched polyester epoxy resin. The room temperature viscosity of the low-viscosity, high-toughness epoxy resin is 0.01-10 Pa·s. The latent curing agent component comprises one or more of the following: dicyandiamide, vinyltriamine, ethylenediamine, methylenebicyclohexaneamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, dipropylenetriamine, dimethylaminopropylamine, m-phenylenediamine, hexahydropyridine, dibenzylamino ether, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, trimellitic anhydride glycerol, polyazelite anhydride, methylhexahydrophthalic anhydride, polysaccharide anhydride, diphenyl ether tetracarboxylic dianhydride, cyclopentadiene tetracarboxylic dianhydride, and linear phenolic resin. The interface enhancement component is a polyalkylsilane resin monomer, which includes one or more of aminopropyltriethoxysilane, (2,3-epoxypropoxy)propyltrimethoxysilane, (methacryloyl)propyltrimethoxysilane, bismaleimide-type triethoxysilane, and cyanate ester-type triethoxysilane.
5. The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement as described in claim 1, characterized in that, The low-dielectric high-toughness resin layer for coating is formed from a low-dielectric high-toughness resin for coating. By weight, the low-dielectric high-toughness resin for coating includes 30-70 parts of low-dielectric epoxy resin copolymer component, 10-25 parts of low-dielectric organic toughening particle component, and 10-25 parts of low-dielectric inorganic rigid particle component, and the low-dielectric high-toughness resin for coating does not contain a curing agent.
6. The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement as described in claim 5, characterized in that, The low-dielectric organic toughening particle component is an organic hollow microsphere, which includes one or more of thermoplastic polyimide hollow microspheres, polyphenylene ether hollow microspheres, polyetheretherketone hollow microspheres, polyaryletherketone hollow microspheres, polyamide hollow microspheres, polyarylether sulfone hollow microspheres, polyethersulfone hollow microspheres, and polyphenylene sulfide hollow microspheres, and the average particle size of the organic hollow microspheres is 1-20 μm; The low-dielectric inorganic rigid particle component is an inorganic hollow microsphere, which includes one or more of the following: silica hollow microspheres, alumina hollow microspheres, titanium dioxide hollow microspheres, zinc oxide hollow microspheres, magnesium oxide hollow microspheres, aluminum hydroxide hollow microspheres, magnesium hydroxide hollow microspheres, ceramic hollow microspheres, barium titanate hollow microspheres, sodium titanate hollow microspheres, boron nitride hollow microspheres, and carbon nanotube modified hollow microspheres. The average particle size of the inorganic hollow microspheres is 100 nm to 20 μm. The low-dielectric organic toughening particle component has a different average particle size than the low-dielectric inorganic rigid particle component.
7. The high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement as described in claim 3 or 5, characterized in that, The low-dielectric epoxy resin copolymer component comprises a low-dielectric epoxy resin monomer and a low-dielectric copolymer component; the low-dielectric epoxy resin monomer is one or more selected from fluorinated epoxy resin, dicyclopentadiene type epoxy resin, biphenyl type epoxy resin, cage-type silsesquioxane modified epoxy resin, alicyclic epoxy resin, and organosilicon modified epoxy resin, and the epoxy equivalent of the low-dielectric epoxy resin monomer is 100-300 g / eq; the low-dielectric copolymer component is one or more selected from cyanate ester, hydrocarbon resin, and benzocyclobutene resin. The cyanate ester is one or more selected from bisphenol A cyanate ester, bisphenol E cyanate ester, bisphenol M cyanate ester, bisphenol F cyanate ester, dicyclopentadiene bisphenol cyanate ester, and phenolic cyanate ester; The benzocyclobutene resin is one or more of monobenzocyclobutene, dibenzocyclobutene, or polybenzocyclobutene containing an imide structure, a fluorine structure, a trifluoromethyl structure, a siloxane structure, an aromatic ether structure, a saturated alkane structure, an unsaturated alkane structure, an amide structure, or a carbonyl structure. The hydrocarbon resin includes one or more of cyclic olefin copolymers, linear olefin copolymers, cyclic olefin homopolymers, and linear olefin homopolymers. The side chains of the hydrocarbon resin have reactive groups capable of reacting with epoxy resin. The reactive groups are one or more of hydroxyl, vinyl, amino, and anhydride groups. The molecular weight of the hydrocarbon resin is 500-50000.
8. A method for preparing a high-toughness, low-dielectric epoxy resin prepreg for automatic fiber placement, characterized in that, Includes the following steps: 1) Preparation of low dielectric resin for impregnation: Mix low dielectric epoxy resin copolymer component, low viscosity high toughness epoxy resin component, interface reinforcement component and latent curing agent component to obtain low dielectric resin for impregnation. 2) Preparation of low-dielectric high-toughness resin for coating: Mix low-dielectric epoxy resin copolymer component, low-dielectric organic toughening particle component and low-dielectric inorganic rigid particle component to obtain low-dielectric high-toughness resin for coating. 3) Preparation of resin film: The low dielectric resin for impregnation is coated to form a low dielectric resin film for impregnation, and the low dielectric high toughness resin for coating is coated to form a low dielectric high toughness resin film for coating. 4) Gradient composite: The impregnation low-dielectric resin film is composited with unidirectional reinforcing fibers, so that the impregnation low-dielectric resin penetrates into the unidirectional reinforcing fibers to obtain a prepreg intermediate; the prepreg intermediate is composited with the coating low-dielectric high-toughness resin film, so that the coating low-dielectric high-toughness resin is coated on the surface of the prepreg intermediate to obtain a wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg. 5) Preparation of fixed-width prepreg bundles: The wide-width automatic fiber placement high-toughness low-dielectric epoxy resin prepreg is cut to obtain fixed-width prepreg bundles.
9. The preparation method according to claim 8, characterized in that, In step 1), 30-50 parts of the low-dielectric epoxy resin copolymer component are heated to melt within a temperature range of 80-110℃. 20-30 parts of the low-viscosity, high-toughness epoxy resin component and 5-10 parts of the interface reinforcement component are added. After stirring until a homogeneous phase is formed, the temperature is lowered to 50-80℃, and 10-25 parts of the latent curing agent component are added. After stirring evenly, the temperature is maintained for 2-5 hours. The viscosity of the low-dielectric resin for impregnation is monitored at 70-80℃ using a rotational viscometer. When the resin viscosity is 7-30 Pa·s, the temperature is maintained and the material is discharged to obtain the low-dielectric resin for impregnation. In step 2), 30-60 parts of the low-dielectric epoxy resin copolymer component are heated to melt within a temperature range of 80-110℃, and 10-25 parts of the low-dielectric organic toughening particle component with an average particle size of 1-20μm and 10-25 parts of the low-dielectric inorganic rigid particle component with a particle size of 100nm-20μm are added. The mixture is stirred until a homogeneous phase is formed to obtain the low-dielectric high-toughness resin for coating.
10. The preparation method according to claim 8, characterized in that, In step 3), a hot-melt prepreg coating machine is used. Within a temperature range of 70-80℃, a sequential coating method is employed. The gap between the coating rollers is adjusted to 0.05-0.25mm, and the roller speed difference percentage is adjusted to 10%-40%. The low-dielectric resin for impregnation is coated to a surface density of 20-300g / m³. 2 The low dielectric resin film used for impregnation has a film accuracy of ±5g / m 2 Using a hot-melt prepreg coating machine, within a temperature range of 80-110℃, a sequential coating method is employed. The gap between the coating rollers is adjusted to 0.05-0.10mm, and the roller speed difference percentage is adjusted to 10%-20%. The low-dielectric, high-toughness resin used for coating is then coated to achieve a surface density of 5-100g / m³. 2 The coating uses a low-dielectric, high-toughness resin film with a film precision of ±5g / m. 2 ; In step 4), the low-dielectric resin film for impregnation and the film with an areal density of 30-400 g / m³ are used. 2 The unidirectional reinforcing fibers are laminated using the first three pressing rollers, with a gap of 0.05-0.15 mm and a pressing temperature of 80-90°C. The prepreg intermediate is then laminated with the low-dielectric, high-toughness resin film for coating using the last three pressing rollers, with a gap of 0.1-0.3 mm and a pressing temperature of 90-120°C. The pressing pressure when the impregnating low-dielectric resin film is laminated with the unidirectional reinforcing fibers is greater than the pressing pressure when the prepreg intermediate is laminated with the low-dielectric, high-toughness resin film for coating. In step 5), the wide-width automatic filament-laying high-toughness low-dielectric epoxy resin prepreg is first-stage coarsely cut to obtain a prepreg narrow strip with a width of 25-200mm. Then, the prepreg narrow strip is second-stage finely cut and prepared into fixed-width prepreg bundles with widths of 3.175mm, 6.35mm, or 12.7mm by a precision slitting machine and winding equipment.